2020
DOI: 10.1177/0361198120917977
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Component Errors in the Highway Capacity Manual Travel Time Reliability Estimations for Urban Streets

Abstract: The Highway Capacity Manual 6th edition (HCM6) includes a new methodology to estimate and predict the distribution of average travel times (TTD) for urban streets. The TTD can then be used to estimate travel time reliability (TTR) metrics. Previous research on a 0.5-mi testbed showed statistically significant differences between the HCM6 estimated TTD and the corresponding empirical TTD. The difference in average travel time was 4 s that, while statistically significant, is not important from a practical persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Because they are all positive it indicates that the TTD for each scenario is positively skewed. Note that most arterial TTDs are positively skewed (6,(15)(16)(17).…”
Section: Empirical Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because they are all positive it indicates that the TTD for each scenario is positively skewed. Note that most arterial TTDs are positively skewed (6,(15)(16)(17).…”
Section: Empirical Data Descriptionmentioning
confidence: 99%
“…Note that there are several HCM6 input parameters that may be adjusted during the calibration process. It was decided to focus on the hour-of-day, day-of-week, and month-of-year demand parameters because it was found that the demand component of the HCM6 TTR model had the greatest impact on the error associated with the HCM6-estimated TTD (6). The goal of the calibration is to adjust the demand parameters such that the resulting estimated HCM6 TTD matches the corresponding empirical TTD for a given case study.…”
Section: Calibrating the Hcm6 Ttd To Empirical Ttdmentioning
confidence: 99%
See 2 more Smart Citations
“…With the recent increase in urban traffic congestion, there has been an increasing need for reliable travel time information. Consequently, travel time reliability (TTR), which attempts to capture the day-to-day variability in travel times, has recently received considerable research interest ( 3 , 4 ).…”
mentioning
confidence: 99%